2018
DOI: 10.3168/jds.2018-14800
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and health of dairy calves given water treated with a reverse osmosis system compared with municipal city water

Abstract: Our objective was to determine effects of drinking reverse osmosis water (RW) versus municipal city water (MW) on growth, nutrient utilization, and health scores of calves. Twenty-four Holstein calves (14 females, 10 males; 2 d old; 44.6 ± 6.10 kg of body weight), housed in individual hutches, were used in a 10-wk randomized complete block design study. Calves were blocked by birthdate and sex. Treatments were RW (Culligan Water Filtration System, Brookings, SD) versus MW (Brookings Municipal Utilities, Brooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Overall BW (Figure 2) and ADG were not different between treatments throughout the study period. (Senevirathne et al, 2017(Senevirathne et al, , 2018. During wk 12, BW were greater (P = 0.05) in calves fed CWS compared with CON.…”
Section: Bw Adg Gain: Feed and Body Frame Growthmentioning
confidence: 93%
“…Overall BW (Figure 2) and ADG were not different between treatments throughout the study period. (Senevirathne et al, 2017(Senevirathne et al, , 2018. During wk 12, BW were greater (P = 0.05) in calves fed CWS compared with CON.…”
Section: Bw Adg Gain: Feed and Body Frame Growthmentioning
confidence: 93%
“…However, there is limited research about the effects of water hardness on milk production or its physicochemical composition. In a recent study, Senevirathne et al (2018) investigated the effects of ad libitum drinking reverse osmosis water (17 mg L −1 , considered soft water) versus municipal/city water (249 mg L −1 , considered very hard water) on growth, nutrient utilization, and health scores of calves. They observed that hard water consumption increased (P = 0.01) mean daily water intake by 5.2%; however, soft water consumption increased (P<0.01) nutrient intake (DMI, crude protein, ether extract, starch, and neutral detergent fiber) at the postweaning period in 5.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Preference was greatest for RW, with MW a close second. However, a follow-up study comparing RW and MW showed similar health yet less water intake of RW with similar animal growth (Senevirathne et al, 2018).…”
Section: Water Preferences Of Young Calvesmentioning
confidence: 93%